The metabolic responses to high carbohydrate meals with different glycemic indices consumed during recovery from prolonged strenuous exercise - Stevenson, E.; Williams, C.; Biscoe, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
This study investigated the metabolic responses to high glycemic index (HGI) or low glycemic index (LGI) meals consumed during recovery from prolonged exercise. Eight male, trained athletes undertook 2 trials. Following an overnight fast, subjects completed a 90-min run at 70% VO2max. Meals were provided 30 min and 2 h following cessation of exercise. The plasma glucose responses to both meals were greater in the HGI trial compared to the LGI trial (P < 0.05). Following breakfast, there were no differences in the serum insulin concentrations between the trials; however, following lunch, concentrations were higher in the HGI trial compared to the LGI trial (P < 0.05). This suggests that the glycemic index of the carbohydrates consumed during the immediate post-exercise period might not be important as long as sufficient carbohydrate is consumed. The high insulin concentrations following a HGI meal later in the recovery period could facilitate further muscle glycogen resynthesis.